/ჲ/-ის გაჩენის კიდევ ერთი შემთხვევა ფშაურში: წაკითხულია მოხსენებად ივანე ლეჟავას დაბადების მე-80 წლისთავისადმი მიძღვნილ სამეცნიერო კონფერენციაზე, თსუ, 22 ნოემბერი, 2024 - ივანიშვილი მარინე (ენათმეცნიერების საკითხები, 2025)
In poetry, the significance of phonetic, morphological, and syntactic structure is interwoven, sometimes even overshadowing the artistic role of verbal tropes. This structure often dominates the poem, transforming into the primary, and sometimes sole, expressive element of its underlying symbolism (Jakobson 1961). The structure of the Georgian (Kartvelian) poem is tonal-syllabic, meaning it is governed by rules concerning syllable placement and the equality of syllable counts within each line. The main organizing principle is the arrangement and regular alternation of verses with a specific syllable count (Gudava 1975). To maintain this balance, poetic language draws on phonetic-phonological, morphological, and syntactic resources of the natural language. Georgian mountain poetry resembles monumental lapidary inscriptions, marked by its depth, delicacy, and beauty. A notable example of Pshavi folklore is the poem Aragvs, sourced from materials of the Giorgi Mtatsmideli Chanting University’s 'Folklore Trip to Pshav' and performed by Nino Naqeuri. Attention is drawn to the clause - the final repeated syllables of the text: aS3Sg.+jvowel devider + ainterrogative particle. -a is an interrogative particle (a similar particle is also reconstructed at the common Kartvelian level) that appears on interrogative words, imparting a questioning tone to the entire sentence. /j/ appears between a word ending in -a and the particle -a, functioning as a midlingual spirant in the phonological system of Pshavi dialect. It holds no independent phonemic value but serves as a variant of the spirants s and h at the boundary of prefix morphemes (Tsotsanidze 1978). cf. in Kakhetian dialect: misdevs > mizdevs (assimilation) > mijdevs. /j/ does not form a syllable; it is articulated with the middle part of the tongue close to the hard palate. When this constriction creates resistance to the outgoing airflow, it takes on a spirant character. In his monograph Pshavi Dialect (1978), G. Tsotsanidze examines the occurrence of /j/ at the boundary of prefix morphemes in detail and provides a corresponding table. /j/ – a palatal approximant, produced by bringing the tongue closer to the soft palate. In the scientific literature, it is often referred to as a “glide”, which suggests it is a transitional sound, as in a diphthong. Another term for it is “semi-vowel”, indicating that, despite its vocalic quality and significant narrowing, the turbulent sound is either not formed or is very weak and does not create a syllable. The poem’s text helps illustrate the distribution of /j/ in Pshavi dialect, particularly in its position within suffix sequences. Interestingly, Gudamakari and Mtiuleti dialects show a similar pattern: after a word ending in -a, /j/ appears between two instances of -a, neither serving as a full syllable nor as the final vowel of the preceding word (movidaj, mok’vdaj, ꭍenaj...). In Mokhevi dialect, however, questions are marked by intonation rather than by the use of /j/ (Shanidze 1989).